The Crc and Hfq proteins of Pseudomonas putida cooperate in catabolite repression and formation of ribonucleic acid complexes with specific target motifs. (2nd June 2014) - Moreno, Renata; Hernández‐Arranz, Sofía; La Rosa, Ruggero; Yuste, Luis; Madhushani, Anjana; Shingler, Victoria; Rojo, Fernando
Summary The Crc protein is a global regulator that has a key role in catabolite repression and optimization of metabolism in Pseudomonads. Crc inhibits gene expression post‐transcriptionally, preventing translation of mRNAs bearing an AAnAAnAA motif [the catabolite activity (CA) motif] close to the translation start site. Although Crc was initially believed to bind RNA by itself, this idea was recently challenged by results suggesting that a protein co‐purifying with Crc, presumably the Hfq protein, could account for the detected RNA‐binding activity. Hfq is an abundant protein that has a central role in post‐transcriptional gene regulation. Herein, we show that the Pseudomonas putida Hfq protein can recognize the CA motifs of RNAs through its distal face and that Crc facilitates formation of a more stable complex at these targets. Crc was unable to bind RNA in the absence of Hfq. However, pull‐down assays showed that Crc and Hfq can form a co‐complex with RNA containing a CA motif in vitro. Inactivation of the hfq or the crc gene impaired catabolite repression to a similar extent. We propose that Crc and Hfq cooperate in catabolite repression, probably through forming a stable co‐complex with RNAs containing CA motifs to result in inhibition of translation initiation.